Morphological and Functional Relationship Between OCTA and FA/ICGA Quantitative Features in AMD-Related Macular Neovascularization - Arrigo, Alessandro; Aragona, Emanuela; Bordato, Alessandro; Amato, Alessia; Borghesan, Federico; Bandello, Francesco; Battaglia Parodi, Maurizio (Frontiers in Medicine, 2021)
Background: The aim was to study the relationship between quantitative information provided by optical coherence tomography (OCT) angiography (OCTA) and conventional angiography in macular neovascularization (MNV) secondary to age-related macular degeneration (AMD). Methods: The research was designed as an interventional, prospective study. We included 66 eyes (66 patients) affected by naïve MNV. Multimodal imaging included structural OCT, OCTA, fluorescein angiography (FA) and indocyanine green angiography (ICGA). The follow-up lasted 1 year. Patients were treated by PRN anti-VEGF injections. Based on FA/ICGA examinations, we divided the patients into two categories: low vessel tortuosity (VT) (< 8.40) and high VT (> 8.40), correlating VT with the MNV area, leakage area, speckled fluorescence (SF) quadrants and MNV area/leakage area ratio. Results: Mean baseline BCVA was 0.50±0.61 LogMAR, improved to 0.31±0.29 LogMAR after one year (p<0.01), with a mean number of 7±2 anti-VEGF injections. Patients revealed type 1 MNV in 36 eyes (55%), mixed type 1 and 2 MNV in 18 eyes (27%), and type 2 MNV in 12 eyes (18%). MNV eyes in high-VT MNV featured poorer BCVA, CMT and OCTA parameters, higher SF quadrants and less exudation, compared with low-VT MNV (p<0.01). Moreover, 30% of high-VT MNV eyes developed outer retinal atrophy. Conclusions: Low VT MNV turned out to be more exudative at baseline but less damaging to the outer retinal structures, whereas high VT MNV proved to be less exudative but more prone to lead to atrophic changes and visual function deterioration. VT may be usefully applied to artificial intelligence-based models designed to characterize MNV secondary to AMD.